Colombia Detailed Assessment of Observance : Key Attributes of Effective Resolution Regimes for Financial Institutions - World Bank (World Bank, Washington, DC, 2016)
At the request of the Colombian authorities, the bank resolution regime was assessed against the Key Attributes of Effective Resolution Regimes for Financial Institutions (KAs). The assessment was conducted by staff of the Financial Stability Board (FSB), International Monetary Fund (IMF) and World Bank utilizing the draft KA Assessment Methodology (AM). The assessment reviewed the resolution regime as of October 2015, and was limited to the banking sector, considering only those elements of the AM that directly relate to bank resolution without assessing those addressing the resolution of insurance firms, investment firms and financial market infrastructures (FMIs). As a draft methodology was used, the findings of the assessment should be viewed as preliminary. A central goal of this assessment was to test the draft AM, and a future revision of the AM might yield different results with respect to the adherence of the Colombian bank resolution regime to the KAs. In this light, no ratings were assigned in this review. This assessment was the first one undertaken in a country that is not a member of the FSB, or home to a Global Systemically Important Financial Institution (G-SIFI).